Inclusive Recruitment of Disabled Workers in Industry 4.0 Era Through the Disability Equality Training Approach - Hamsinah B.; Umi Rusilowati; Fitri Marsela; Taswanda Taryo (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2025)
Disabled workers are needed to work optimally in their fields of formal sectors and to minimize the lack of training for internal staff to build a supportive work environment by HRD (human resource development). a specifically-specialized training regarding the potential and characteristics of disabled workers is required. The aim of this research is to examine the need for a special method to make disabled workers truly acceptable in the formal sector, both government and private. A mixed method that can bridge this gap includes Disability Equality Training (DET) which increases companies' understanding and awareness of the rights, potential, and needs of disabled workers. The results showed managerial policies and commitment, reflected in organizational awareness to view disability as part of human resource diversity, not as an individual limitation. The government is advised to integrate DET into their HR management strategies and ensure accessible and inclusive digital recruitment systems. Governments and policymakers need to strengthen regulatory support and encourage cross-sector collaboration to expand employment opportunities for disabled workers. More organizations and industry sectors need to develop a more comprehensive inclusive recruitment model within the context of digital transformation.